Polychaete trunk neuroectoderm converges and extends by mediolateral cell intercalation - Steinmetz, Patrick R. H.; Wittbrodt, Joachim; Arendt, Detlev (Proceedings of the National Academy of Sciences of the United States of America, 2007)
During frog and fish development, convergent extension movements transform the spherical gastrula into an elongated neurula. Such transformation of a ball- into a worm-shaped embryo is an ancestral and fundamental feature of bilaterian development, yet this is modified or absent in the protostome model organisms Caenorhabditis or Drosophila. In the polychaete annelid Platynereis dumerilii, early embryonic and larval stages resemble a sphere that subsequently elongates into worm shape. Cellular and molecular mechanisms of polychaete body elongation are yet unknown. Our in vivo time-lapse analysis of Platynereis axis elongation reveals that the polychaete neuroectoderm converges and extends by mediolateral cell intercalation. This occurs on both sides of the neural midline, the line of fusion of the slit-like blastopore. Convergent extension moves apart mouth and anus that are both derived from the blastopore. Tissue elongation is actin-dependent but microtubule-independent. Dependence on JNK activity and spatially restricted expression of strabismus indicates involvement of the noncanonical Wnt pathway. We detect a morphogenetic boundary between the converging and extending trunk neuroectoderm and the anterior otx-expressing head neuroectoderm that does not elongate. Our comparative analysis uncovers striking similarities but also differences between convergent extension in the polychaete and in the frog (the classical vertebrate model for convergent extension). Based on these findings, we propose that convergent extension movements of the trunk neuroectoderm represent an ancestral feature of bilaterian development that triggered the separation of mouth and anus along the elongating trunk.